The relationship of smoking and unhealthy alcohol use to the HIV care continuum among people with HIV in an integrated health care system. (1st February 2021) - Satre, Derek D.; Levine-Hall, Tory; Sterling, Stacy A.; Young-Wolff, Kelly C.; Lam, Jennifer O.; Alexeeff, Stacey; Hojilla, J. Carlo; Williams, Andrew; Justice, Amy C.; Sterne, Jonathan; Cavassini, Matthias; Bryant, Kendall J.; et al.
Highlights: Smoking and unhealthy alcohol use may adversely impact the HIV continuum of care. We examined continuum outcomes among people with HIV in an integrated health system. Smoking was adversely associated with HIV care continuum outcomes. Unhealthy alcohol use was not independently associated with outcomes. Abstract: Introduction: Smoking tobacco and unhealthy alcohol use may negatively influence HIV care continuum outcomes but have not been examined in combination. Methods: Participants were people with HIV (PWH) in Kaiser Permanente Northern California. Predictors included smoking status and unhealthy alcohol use (exceeding daily and/or weekly limits) reported by patients during primary care screening (index date). Outcomes were based on not achieving the following steps in the care continuum: linkage to HIV care (≥1 visit within 90 days of newly identified HIV diagnosis), retention (2+ in-person visits, 60+ days apart) and HIV RNA control (<75 copies/mL). Adjusted odds ratios (ORs) were obtained from separate logistic regression models for each outcome associated with smoking and unhealthy alcohol use independently and combined. Results: The overall sample (N = 8958) had a mean age of 48.0 years; was 91.3 % male; 54.0 % white, 17.6 % Latino, 15.1 % black, and 9.6 % other race/ethnicity. Smoking was associated with higher odds of not being linked to HIV care (OR = 1.60 [95 % CI 1.03−2.48]), not retained (OR = 1.30 [95 % CI 1.13−1.50]), and HIV RNA not in control (OR = 1.91 [95 % CI 1.60−2.27]). Alcohol measures were not independently associated with outcomes. The combination of unhealthy alcohol use and smoking (versus neither) was associated with higher odds of not being linked to care (OR = 2.83 [95 % CI 1.40−5.71]), although the interaction did not reach significance (p = 0.18). Conclusions: In this large sample of PWH in an integrated health care system, smoking, both independently and in combination with unhealthy alcohol use, was associated with worse HIV care continuum outcomes.